A Year of Endoscopic Retrograde Cholangiopancreatography (ERCP) At a Glance. Indications, Interventions, Complications - Kazmi, Syed Kumail Hasan; Ali Khan, Rao Saad; Alam, Laima; Saeed, Farrukh (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the demographics, indications and frequency of interventions and complications endoscopic retrograde cholangiopancreatography (ERCP). Study Design: Cross-sectional study. Place and Duration of Study: Department of Gastroenterology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Dec 2019. Methodology: The study included all the elective and emergency ERCP procedures from January 2019 to December 2019. Results: Out of 1030 patients who underwent endoscopic retrograde cholangio-pancreaticography, 903 were enrolled. Sixtyone percent of the participants were males. The mean age was 56 ± 16 years, with the majority of the patients lying in the age range of 41-65 years. The most common indication for ERCP in this study was choledocholithiasis (47%), the most common complication encountered was acute pancreatitis (2.1%), and a mortality rate of 0.2% was reported. The complication rate was statistically related to the intervention rather than the age and gender of the patients. Conclusion: The most common indication for ERCP remains choledocholithiasis, with the most common ERCP complication being acute pancreatitis followed by stent migration. Biliary fistulae, post-surgical biliary leaks and strictures, pancreatic pseudo cysts, acute cholangitis, choledocholithiasis and cholestasis secondary to as cariasis were found in a relatively younger group. The success rate was above 95% for high volume centres.